Cultural intelligence: Concepts and definition statements - A. Solomon; R. Steyn (South African Journal of Business Management, 2017)
The rapid rate of globalisation is increasingly exposing both individuals and organisations to situations of cultural heterogeneity in which they are expected to function optimally. The cultural intelligence research programme has consequently experienced increased impetus with the result that a broad array of insights now exists. Organising such information will facilitate the assimilation thereof by both business representatives and scholars. Accordingly, this review sought to situate the cultural intelligence literature in terms of the concept and definition statement elements of the general body of scientific knowledge framework. A systematic literature review followed by content analysis was performed. Concepts were crystallised through a fusion of the key words whilst the definition statements were examined to detect elements of both uniqueness and commonality. Despite a large volume of key words existing across the material, remarkably only a limited number of concepts were identified: accomplishment, culture, expatriates, experience, fit, intelligence, motivation, supervision and training. Whilst the definition statements of cultural intelligence have evolved to include, amongst others, its dimensions, the range of culture types it exists in relation to, the categories of persons that may demonstrate it and the conditions in which it could be exhibited, they mostly remain predicated upon the initial expositions.
Keywords: 650